Social media and knowledge management disruptive technology - Noordin, Mohamad Fauzan; Othman, Roslina; Hamood Rageh Rassa, Anhar (Universiti Utara Malaysia, 2018)
Social media emerged as a disruptive technology that has brought many advantages in different fields beyond communication and socialization. However, social media lacks the consideration of knowledge management utility, which leads to the creation of several negative impacts such as fake news, data manipulation, Cambridge Analytica. These bad effects contribute to the decreasing level of trustworthiness, truthfulness and accountability of these disruptive technologies besides the emergence of an unstable economy, politics, and society. Therefore, knowledge management and code of ethics should govern the utilisation of this disruptive technology to overcome the negative effects. Social media use should be governed based on the objectives of Syari’ah (Maqasid Al- Syari’ah): Daruriyat, Hajiyat and Tahsiniyat. The five values of protection include: religion, life, intellect, lineage and property. The best example of interaction should be derived from the Madani Society.